2018
DOI: 10.4000/samaj.4451
|View full text |Cite
|
Sign up to set email alerts
|

Ruling on Rituals: Courts of Law and Religious Practices in Contemporary Hinduism

Abstract: Scholars have regularly pointed out that in secular states the involvement of courts in religious matters is commonplace. There are two main reasons for this. One is that in the modern state, "religion is, in part, constituted by means of law, but simultaneously as something that is constituted to stand at arm's length from the law" (Lambek 2013:1). 1 The second follows on from the first: as Jurinski (2004:3) remarks in the case of the USA, "the courts have become arbiters of what kinds of restrictions the gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…First, there is the distinction that post-colonial courts made between religion and superstition, influenced by nineteenth-century Hindu reformist movements such as the Brahmo Samaj and the Arya Samaj that wanted to 'purify' Hinduism of what they called 'evil practices'. Second, there is the distinction between the essential part of religionwhich enjoys constitutional protection and for which the principle of non-interference, in line with the 2015 constitution, has been reaffirmed -and the non-essential part, which extends to superstitious practices, which may be abrogated in the name of social progress (Tarabout 2018).…”
Section: Contesting Sacrifice As Violence Inflicted On Groupsmentioning
confidence: 99%
“…First, there is the distinction that post-colonial courts made between religion and superstition, influenced by nineteenth-century Hindu reformist movements such as the Brahmo Samaj and the Arya Samaj that wanted to 'purify' Hinduism of what they called 'evil practices'. Second, there is the distinction between the essential part of religionwhich enjoys constitutional protection and for which the principle of non-interference, in line with the 2015 constitution, has been reaffirmed -and the non-essential part, which extends to superstitious practices, which may be abrogated in the name of social progress (Tarabout 2018).…”
Section: Contesting Sacrifice As Violence Inflicted On Groupsmentioning
confidence: 99%
“…73 A rich body of jurisprudence on law and religion has developed in India following various lines of enquiry. These enquiries are entrenched mainly in the idea that religion is a robust social force, is in part constituted by law, 74 but is simultaneously something to be kept at a distance from the law. 75 In the context of declaring idols as legal entities, for example, Indian courts have observed that 'if the people believe in the temples' religious efficacy, no other requirement exists'.…”
Section: Rationale Protection Of Faithmentioning
confidence: 99%
“…38.For historical scholarship on how the proper domain of law vis-à-vis tradition has been debated, see: Mani (1987), Sarkar (2008). For commentary on Courts’ adjudication in the realm of ‘law and religious practices’, see Tarabout (2018). …”
mentioning
confidence: 99%